Performance of the Banking Investment Portfolio According to the Indicators Applied Research - Sadeq Hussein Abdulhasan, Mokhalad Hamzah Jaddoa, Shaymaa Mahdi Kadhim, (Opción, 2019)
The research tool consisted of quantitative models to evaluate the performance of the financial management leaders represented by (Sharp, Treynor, and Jensen) indicators to evaluate the performance of the investment banking portfolio for six years (2010-2015). The results showed a discrepancy between banks’ portfolios performance among the indicators used for the test. In conclusion, banks should study all aspects of return and risk levels and use diversification to obtain an optimal portfolio of investments to avoid the risks of significant economic fluctuations.